THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK MOTIVATION, AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT SOLUSI MITRA ANUGERAH SIDOARJO - Remianus Klau; Hafidulloh; Gogi Kurniawan; Dani Romati (Journal of Management and Innovation Entrepreneurship (JMIE), 2026)
This study examines the relationship between transformational leadership, work motivation, compensation, and employee performance at PT Solusi Mitra Anugerah Sidoarjo. The study employed a quantitative correlational research design involving 45 employees selected using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using Spearman Rank Correlation because the data were not normally distributed. The findings indicate that transformational leadership, work motivation, and compensation each have a positive and significant relationship with employee performance. Among the examined variables, transformational leadership demonstrates the strongest relationship with employee performance. Furthermore, the combined explanatory contribution of the three variables is reflected in a Pseudo R-Square (Nagelkerke) value of 0.970, indicating that transformational leadership, work motivation, and compensation account for approximately 97% of the variation in employee performance. The study concludes that strengthening transformational leadership, supported by enhanced employee motivation and fair compensation practices, is essential for improving employee performance in service organizations.